2012
DOI: 10.22146/ijc.21338
|View full text |Cite
|
Sign up to set email alerts
|

<i>IN VITRO</i> INHIBITION OF CELERY (<i>Apium graveolens</i> L.) EXTRACT ON THE ACTIVITY OF XANTHINE OXIDASE AND DETERMINATION OF ITS ACTIVE COMPOUND

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
1
7
1
1
Order By: Relevance
“…Total phenolic and flavonoids contents are found to positively correlated with total antioxidant capacity of apiaceous plants. 17 However, in the current study we found by EPR spectroscopy that ADSh and MPR were to be a venerable hydroxyl radical scavenger even in low concentration, although it's TPC and TFC weren't the highest. Also, the low hydroxyl radical quenching capacity at low concentration attributed to ADF was expected as it possesses the low total phenol content but moderate flavonoid content was observed.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Total phenolic and flavonoids contents are found to positively correlated with total antioxidant capacity of apiaceous plants. 17 However, in the current study we found by EPR spectroscopy that ADSh and MPR were to be a venerable hydroxyl radical scavenger even in low concentration, although it's TPC and TFC weren't the highest. Also, the low hydroxyl radical quenching capacity at low concentration attributed to ADF was expected as it possesses the low total phenol content but moderate flavonoid content was observed.…”
Section: Discussioncontrasting
confidence: 66%
“…Iswantini et al inferred that extract proved to be a potential scavenger for free OH• radical when it has the percent inhibition value greater than 50%. 17 At 10 mg/ml, all the tested extracts were quenched EPR signals from DMPO-HO• adduct (more than 85%), but at range 0.5-2 mg/ml signals scavenged to varying degrees. Methanol parsley roots extract (MPR) was perplexing in prohibiting formation of the DMPO-HO• adduct by 98.90 % at 10 mg/ml concentration.…”
Section: In Vitro Hydroxyl Radical (•Oh) Scavenging Ability Using Eprmentioning
confidence: 89%
“…Based on (Table I) shows that the addition of celery stems infused water extract has lower uric acid uptake compared to the leaves infused water extract. Iswantini (2012) tested the roots of celery and their plants using maceration methods. The results of the Iswantini (2012) study show that the lower part of the plant, the celery root has a better inhibition activity than the plant part.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the concentration‐dependent hydroxyl radical scavenging potency of A. graveolens extracts expressed as % inhibition of the EPR‐detected DMPO‐HO• radical adduct. Crude extracts and/or fractions exhibited potential scavenging effect for free •OH radical when exhibiting a percent inhibition value greater than 50% (Iswantini, Ramdhani, & Darusman, 2012). At 10 mg/ml, all Apium extracts were able to quench EPR signals due to DMPO‐HO• adduct, but at lower doses of 0.5–2 mg/ml signals scavenged to varying degrees.…”
Section: Resultsmentioning
confidence: 99%